Factors influencing future workforce readiness for digital transformation among SCM students: A study at Polytechnic Seberang Perai - Kanchana, Kannan (2025)
The supply chain industry is experiencing pressure to integrate digital technologies into its operations, creating demand for a tech-savvy and future resilient workforce. This study investigates the readiness of Malaysia’s Technical and Vocational Education and Training (TVET) students for digital transformation in logistics and supply chain field. As the industry revolution reshapes the workforce demands, this research (1) investigates the level of digital literacy skill, (2) examines the relationship of digital literacy skills, training development, and curriculum towards future workforce readiness, (3) analyses the significant differences of future workforce readiness among different group of students. A purposive sampling technique and self-administrated questionnaire was employed to collect data of 174 students from Semester 4, Semester 5 and Semester 6 (Internship) students enrolled in the Diploma in Logistics and Supply Chain Management at Polytechnic Seberang Perai, Penang. Descriptive analyses revealed, that student have high level of digital literacy skill. Pearson’s correlation analysis indicated a strong positive relationship between digital literacy skills, training development and curriculum towards workforce readiness. Analysis of variance (ANOVA) results showed no statistically significant differences across group of students, indicating workforce readiness is not influenced by different semester level. The findings of this research suggested that there is a need to strengthen digital literacy skills development, regularly update of curriculum, and provide continuous access to digital learning infrastructure. This study contributes to TVET institutions and policy-makers by providing empirical evidence to develop strategies which provide technology access, aligns curriculum with skill development to produce a resilient supply chain workforce.